Does grid-connected clean power promote regional energy efficiency? An empirical analysis based on the upgrading grid infrastructure across China. (10th June 2018) - Wang, Yongpei; Yan, Weilong; Zhuang, Shangwen; Li, Jun
Abstract: On the basis of the fact that China is setting up world's largest electricity network with the extra high voltage (EHV) and ultra high voltage (UHV) as their backbones, creating the foundation for large-scale accession of clean power which may deeply affect regional energy efficiency across the country, this paper attempts to empirically study the joint effects of clean power accessing to power grids on regional total-factor energy efficiency. To complete this job, we first measured the total-factor energy efficiencies of 29 provinces in China over the period 1991–2013, based on one of the data envelopment analysis methods, then, the static panel model considering panel fixed effect with instrument variable (FE-IV), dynamic panel model of system generalized method of moments (SYS-GMM) and panel smooth transition regression (PSTR) were employed, respectively, to investigate separate and joint effect of clean power and its grid-connection with EHV and UHV electricity network. The results show that the joint effect of clean power accessing to EHV and UHV power grid is either not significant or even negative although clean power itself separately promote regional energy efficiency. Thus, while the investment in grid infrastructure continues to increase, the grid-connection mechanism of clean power needs to be optimized therewith. Graphical abstract: (a) HV density of China's provinces in 1992 and 2013. (b) EHV density of China's provinces in 1992 and 2013.Image 1 Highlights: China has built large-scale of extra high voltage (EHV) and ultra high voltage (UHV) grid infrastructure. Clean power indeed promote regional total factor energy efficiency. The joint effects of clean power and EHV and UHV power grid are either negative or not significant. The relationship between geographic density of EHV power grid and clean power is V-shaped with regional GDP.